The prophet of Yonwood - DuPrau, Jeanne (DuPrau, Jeanne. Ember, 2006)
While visiting the small town of Yonwood, North Carolina, eleven-year-old Nickie makes some decisions about how to identify both good and evil when she witnesses the townspeople's reactions to the apocalyptic visions of one of their neighbors.